Exploring biomedical applications of phenylboronic acid— functionalized chitosan conjugates - Brahmam Bheemisetty, Shaila Angela Lewis (Journal of Applied Pharmaceutical Science, 2024)
Chitosan (CS), a cationic polysaccharide has received increasing attention ever since it entered into the pharmaceutical domain due to excellent biocompatibility, biodegradability, and high chemical reactivity. Evidence from the literature reveals that chemical modification on the primary amine group or the hydroxyl group of CS can augment its application to achieve a specific biomedical application. Phenylboronic acid (PBA) and its moieties are known to form covalent bonds with polyol compounds and have thus allured researchers owing to their enormous potential. The conjugation of these two moieties has shown to exhibit a plethora of properties that can be exploited for a variety of applications. In this review, an effort is made to compile different PBA derivatives conjugated to CS and showcase their potential. An important application of these conjugates is their ability to function as glucose-sensitive polymers which enables self-regulated insulin release in the treatment of diabetes besides functioning as a diagnostic agent. Also, the noteworthy use of these conjugates has been in wound healing and tumour targeting. This review gives an overview of research undertaken with CS-PBA highlighting their applications to make the reader aware of their enormous potential
Keywords: Chitosan, tumor targeting, conjugate, phenylboronic acid, glucose sensing